An Explorative Study on the Impact of an Individual’s Self –Esteem on Performance: Exploring the relationship between self-esteem and performance (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Study is entitled “An explorative study on the Impact of an Individual’s Self –Esteem on Performance” Just as our body needs exercise and good nutrition to stay fit and healthy, so too our mind needs the right conditions for us to have a healthy self esteem. When the conditions of our mind is poor, our self esteem will also be poor, not only we are what we eat, we are also essentially what we think because what we think affects how we feel and how we feel determines the actions we take. Through this research trying to find out the impact of Self-esteem on the Performance of the most important age group